The effects of the Richmondian invasion on benthic invertebrate functional diversity during the Late Ordovician - Ess, Madeline P.; Banker, Roxanne M. W.; Maciech, Samantha A.; Dineen, Ashley A.; Roopnarine, Peter D.; Tyler, Carrie L. (Frontiers in Ecology and Evolution, 2026)
Rising temperatures and globalization are enabling widespread biotic invasions today, particularly in marine environments. While the long-term consequences of invasion are poorly understood, the fossil record can be used to assess the impacts of past invasions on ecosystem structure and functioning on evolutionary timescales. During the Late Ordovician (Katian), 445.25 million years ago, deglaciation and subsequent rising sea level connected formerly isolated shallow epicontinental seas, facilitating the invasion of over 75 genera through larval dispersal in several pulses known as the Richmondian Invasion. Here we examine 1,139 species from these benthic marine communities of the Cincinnati Arch (USA) to quantify the effects of invasive species on functional diversity, which has been shown to influence ecosystem dynamics, stability, productivity, and functioning. Changes in functional diversity were quantified across six 3rd-order stratigraphic sequences to assess the impacts of invasion using functional traits readily identifiable in fossil taxa: tiering above the substrate, feeding mode, motility/attachment, structural robustness, trophic rank, vision, and body form. We find that despite well documented changes in community composition, the arrival of invaders did not significantly add new functional entities or dramatically alter functional diversity, and invaders largely occupied pre-existing functions. While there were changes across the invasion, community structure ultimately returned to a state similar to the pre-invasion community. This suggests that despite changes in community composition across the Richmondian Invasion, ultimately the invasion did not substantially restructure functional diversity, as we observed little change in the number of functions, functional redundancy and over redundancy, vulnerability, and the distribution of species among functional entities. These findings emphasize the decoupling of changes in community composition and functional diversity, and the importance of functional diversity in assessing the potential ecological impacts of marine invasions today.